Исследование метрологических параметров датчиков на основе pН-чувствительных полевых транзисторов - Kukla, A. L.; Lozovoy, S. V.; Pavluchenko, A. S.; Nagibin, S. N. (PE "Politekhperiodika", Book and Journal Publishers, 2013)
Primary semiconductor electrodes based on the dual channel pH-sensitive field effect transistors were investigated to characterize their performance both to determine pH value of test solution and to measure sensor responses in differential mode. The simplified three-lead sensor design has been implemented for these purposes. It is shown that such parameters as accuracy, repeatability and stability of developed sensors satisfy necessary requirements for typical laboratory applications.